Determinação dos efeitos do gossipol sobre o ciclo estral, a foliculogênese e o desenvolvimento embrionário precoce de roedores e galinhas - Lelis, Ivana Cristina Nunes Gadelha (Universidade Federal Rural do Semi-Árido, 2015)
Gossypol is a phenolic compound produced by pigment glands in cotton stems, leaves, seeds and flower buds (Gossypium spp). Cottonseed meal is a by-product of cotton that is used for animal feeding because it is rich in oil and proteins. However, gossypol toxicity limits cottonseed use in animal feed. High concentrations of free gossypol may be responsible for acute clinical signs of gossypol poisoning, the most common toxic effect is a reduction in reproduction of males and females. The objective of this study was to evaluate the effects of gossypol in the estrous cycle, folliculogenesis in vivo and in vitro and in developing embryos in vitro rodent and chickens. For the first experiment were used 24 Wistar rats divided into two groups: a control group (saline injection, subcutaneously) and the other treated with gossypol (25 mg/kg/day subcutaneously) for 15 days. The rats were euthanized after the last day of treatment for blood and fragments of ovaries, uterus and thyroid. Blood was collected for hormone analysis by ELISA and the ovaries were collected for histological study for qualitative and quantitative evaluation of ovarian follicles. For the second experiment, it took 32 ovaries of female rats and mice and four chickens. The ovaries of rats and mice, chickens and fragments ovary cells were grown in 24-well culture plates containing 1 ml of culture medium specific. We tested four concentrations of gossypol: 0 (control), 5, 10 and 20 µg / ml. All plates were incubated at 39 ° C and 5% CO2 for 24 hours and seven days. After incubation, the ovaries were fixed and processed for histological analysis. For the third experiment, nulliparous female Balb-C mice were superovulated and then allocated to males. Next day, harvest embryos was performed in 2-8 cell stage. Sequential washes the tubes were performed to remove the embryos on modified HTF. Lots 5 - 8 are selected embryos collected and transferred to new culture HTF medium without HEPES supplemented with 10% FBS. Subsequently they were collected and deposited into microdroplets (30 µ L) medium supplemented in 35x10 mm plates. The embryos were cultured in medium without addition of gossypol (control group) or with concentrations of 5, 10 and 20 µg / ml of gossypol added to each drop. These droplets were immersed in mineral oil and grown in a glasshouse with 5% CO2 at 37 ° C for 24 hours. After the cultivation, the embryos were stained for the detection of ruptured membranes and cells in cell death. It can be seen that gossypol promotes degeneration of ovarian follicles and embryolethality and this toxicity occurs by direct action of gossypol and not a product of its biotransformation
Determination of gossypol effects on the estrous cycle, folliculogenesis and early embryonic development of rodent and chickens
Keywords: Cotton; Gossypium; Anti-nutritional factor; Algodão; Gossypium; Fator Anti-nutricional; CIENCIAS AGRARIAS::MEDICINA VETERINARIA